Exceeding the limits of paediatric heat stress tolerance: the risk of losing a generation to climate inaction - Sulani Nyimbili; Anna Bershteyn; Alexander Azan; Oyinkansola O Babayode (BMJ Paediatrics Open)
Greenhouse gas (GHG) emissions are creating unprecedented climate-driven extreme weather, with levels of heat and humidity surpassing human physiological tolerance for heat stress. These conditions create a risk of mass casualties, with some populations particularly vulnerable due to physiological, behavioural and socioeconomic conditions (eg, lack of adequate shelter, limited healthcare infrastructure, sparse air conditioning access and electrical grid vulnerabilities). Children, especially young children, are uniquely vulnerable to extreme heat-related morbidity and mortality due to factors including low body mass, high metabolism, suboptimal thermoregulatory mechanisms and behavioural vulnerabilities. Children are also uniquely vulnerable to non-fatal heat-related morbidities, including malnutrition due to agricultural disruptions and cardiometabolic, respiratory and mental illnesses from heat exposure and/or confinement during heat avoidance. Climate mitigation through GHG reductions is central to reducing harms to children and preventing the loss of a generation to climate change. In regions most predisposed to extreme heat-driven mass casualties under various GHG emission scenarios—particularly South Asian and Southwest Asian and North African regions—adaptation tools specific to children’s needs are the most urgently needed. Existing public health interventions (eg, cooling infrastructure and preventative educational campaigns) to reduce acute heat mortality, and medical infrastructure capacity to treat heat-related illnesses are currently inadequate to meet children’s growing heat resiliency needs. Paediatricians and other clinical and community child healthcare providers in these regions lack education about children’s heat risks and adaptation tools. Paediatricians and other child healthcare providers have a crucial role in research, education, clinical practice and advocacy to protect children during extreme heat events. Paediatricians, other child healthcare providers and stakeholders of children’s well-being are urged to act on young children’s behalf and to elevate youth leadership in GHG mitigation and extreme heat adaptation policy-making.